Lethal acute amigdalitis caused by Streptococcus pyogenes - Ibara Tanaka, Ioshie; Hirochi Iwamoto, Airton; Person, Osmar Clayton (O Mundo da Saúde, 2009)
Streptococcus pyogenes is a gram positive bacterium that constitutes the main cause of pharyngoamigdalitis in adults and children. Acute streptococcal amigdalitis cases are more frequent at cold times of the year, being contagious through direct contact with secretions of the respiratory tract. Frequently they are controllable. However, from the primary oropharyngeal focus of infection, it may affect different organs and tissues of the organism, causing serious suppurative complications. The present study aimed to describe two clinical cases of patients with acute amigdalitis who developed septicemia and died: one of the patients was a child and the other an adult. In both cases, S. pyogenes was isolated in blood culture and the patients came to die due to septicemia. Although direct association between the cases cannot be made, one may conclude that bacterial oropharyngeal infections must be treated as earlier as possible and that they require us to consider the aggressive potential of some lineages of S. pyogenes in cases that last more than five days or present an atypical clinical evolution.